2016
DOI: 10.17780/ksujes.16070
|View full text |Cite
|
Sign up to set email alerts
|

Masonry Infill Walls Effect In Short Column Formation In Rc Buildings: A Case Study

Abstract: ABSTRACT:The analyses of infill frame structures are generally done ignoring the presence of brick masonry in the analytical models but it is a prevalent mistake. Behaviors of such buildings vary significantly during the earthquake events. The lateral resisting capacity of infill wall actually restricts the column only up to the wall height but above the wall height, the free column deforms easily. In this paper, the effect of infill wall in formation of short column at military aid watchtower in Turkey has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…However, analytical and experimental studies have revealed that infill walls decrease story drift against horizontal loads, provide strength and stiffness to a structure, and thus all this effect cannot be ignored (Kaplan, 2008;İrtem et al, 2005;Beklen and Çağatay, 2009;Sevil et al, 2010;Beklen, 2009;Mehrabi et al, 1996;Murty and Jain, 2000). Yet, along with the contributions of infill walls stated above, there are also other studies available showings that they affect the behavior of a structure in a negative way (Akkuzu, 2007;Yadollahi et al, 2016). The design choices, such as using infill walls only in one axis of a structure, changing the area and position between stories of infill walls , forming ribbon windows ( Figs.…”
Section: Introductionmentioning
confidence: 98%
“…However, analytical and experimental studies have revealed that infill walls decrease story drift against horizontal loads, provide strength and stiffness to a structure, and thus all this effect cannot be ignored (Kaplan, 2008;İrtem et al, 2005;Beklen and Çağatay, 2009;Sevil et al, 2010;Beklen, 2009;Mehrabi et al, 1996;Murty and Jain, 2000). Yet, along with the contributions of infill walls stated above, there are also other studies available showings that they affect the behavior of a structure in a negative way (Akkuzu, 2007;Yadollahi et al, 2016). The design choices, such as using infill walls only in one axis of a structure, changing the area and position between stories of infill walls , forming ribbon windows ( Figs.…”
Section: Introductionmentioning
confidence: 98%